Intracellular localization of the high molecular weight microtubule accessory protein by indirect immunofluorescence (The Rockefeller University Press, 1978)
Microtubule accessory proteins were isolated from porcine brain microtubules by phosphocellulose chromatography, and the high molecular weight protein (HMW protein), purified from this microtubule-associated fraction by electrophoretic elution from SDS gels, was used to raise antisera in rabbits. In agarose double diffusion tests, the antiserum obtained forms precipitin lines with purified HMW protein but not with tau protein or tubulin. When rat glial cells (strain C6) are examined by indirect immunofluorescence, this serum specifically stains a colchicine-sensitive filamentous cytoplasmic network in interphase cells, a network indistinguishable from that seen when cells are treated with antitubulin serum. In dividing cells, specific staining of the mitotic spindle and the stem body is observed with the antiserum to HMW protein. These studies indicate that HMW protein, like tau protein, is associated with microtubules in intact cells.